Strategic groups and competitive groups in the UK pharmaceutical industry 1993-2002 - Leask, Graham (Cranfield University, 2004)
Strategic group research originated in the 1970s and a number of notable studies centered on the US pharmaceutical industry. Results were however, conflicting. This thesis explores the nature of strategic groups and the related concept of competitive groups in the UK pharmaceutical industry during the period 1993 to 2002. The research follows three related themes. The first research theme identifies two stable strategic time periods each of five years duration across the period studied. Within each of these time periods strategic groups were identified using a combination of Ward's method and aK means clustering algorithm and the presence of a relatively stable strategic group structure was confirmed. A statistically significant relationship between these strategic groups and performance is demonstrated using three performance measures. The second research theme then explores the movement of firms between strategic groups and finds some support for the proposition that firms moving between strategic groups move to more advantageousp ositions. The relationship between strategicg roups and mergers is also investigated and this research finds that mergers between firms occur preferentially across strategic groups rather than within strategic groups. This relationship is confirmed as highly statistically significant. Finally in the third research theme the relationship between strategic groups, how firms compete and competitive groups, where firms compete, are investigated. Six different competitive groups are identified, all but one of which is concentrated around a dominant therapeutic area. This finding suggests that direct competition between firms is reduced by market segmentation. A weak relationship was found between competitive groups and performance but when competitive groups (where firms compete) and strategic groups how firms compete) are examined in combination a strong statistically significant relationship with performance was found.